Respuesta :
Answer:
x^4+100x^2-5x^2-500=0
x^2(x^2+100)-5(x^2+100)=0
(x^2+100)(x^2-5)=0
from first expression
x^2+100=0
x^2=-100
x= root under -100
Therefore x=-10
from next expression
x^2-5=0
x^2=5
Or x=2.23
Step-by-step explanation:
Answer:
x = ± sqrt(5)
x = ±10i
Step-by-step explanation:
x^4+ 95x^2-500=0
What two numbers multiply to -500 and add to 95
-5 * 100 = -500
-5 +100 = 95
(x^2 - 5) (x^2 + 100) = 0
Using the zero product property
x^2 -5 =0 x^2 +100 =0
x^2 -5+5 =0 x^2 +100-100 = 0-100
x^2 =5 x^2 = -100
Take the square root of each side
x = ± sqrt(5) x = imaginary numbers
x = ±10i